World Bank Resilience M&E : Good Practice Case Studies - World Bank Group (World Bank, Washington, DC, 2017)
These case studies were developed as part of the World Bank's Results Monitoring and Evaluation for Resilience Building Operations (ReM&E) project, which aims to develop and increase the application of systematic, robust, and useful approaches to monitoring and evaluation (M&E) for resilience-building projects/programs within the World Bank. The case studies propose to foster a grounded understanding of good ReM&E practices through real-world examples. The intended audiences are Task Team Leaders (TTLs) and operational staff of the World Bank who design and/or oversee the implementation of M&E for resilience-building operations, as well as their counterparts at other development organizations.